Lessons from the Marshall Plan - Eichengreen, Barry (World Bank, Washington, DC, 2017)
The Marshall Plan is invoked whenever policy makers contemplate large-scale foreign aid. A cursory Google search turns up 'A Marshall Plan for Africa,' 'A Marshall Plan for Haiti," 'A Marshall Plan for Eastern Europe,' and 'A Marshall Plan for the East.' The foreign aid program officially known as the European Recovery Program (ERP), but forever associated with the name of Secretary of State George C. Marshall, is widely regarded as a singular success. Over the four years from 1948 through 1951, the United States transferred $13 billion (roughly $115 billion at current prices) to the war-torn nations of Europe. The transfer represented approximately two per cent of U.S. Gross Domestic Product (GDP) and roughly the same share of the collective GDP of the recipient countries. The recipients, seemingly on the brink of economic collapse, mounted a strong recovery. Industrial production in the recipient European countries leapt from just 87 per cent of pre-Second World War levels in 1947 to fully 135 per cent in 1951, a 55 per cent jump in just four years. At least as importantly, the resumption of growth was sustained. Europe embarked on a 'golden age' of economic growth that spanned a period of decades. No wonder, then, that the Marshall Plan is widely regarded as the most striking historical example of a successful large-scale foreign aid program. And no wonder that there have been repeated attempts to identify the key ingredients of its success in the hope that this might be replicated in other times and places.